Study of Plasma Cholesterol in Adults with Phenylketonuria - Ambreen Ali, Nayab Sarwar, Lala Naeem Butt, Maria Tasneem Khattak, Ashfaq Ahmad Shah Bukhari, Umair Wadood, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study was designed to employ the NMR lipoprotein profiling technique to evaluate the spectrum of total cholesterol, LDL cholesterol, and HDL cholesterol. The major aim of this research was to investigate the subclasses of lipoprotein to investigate the pathophysiology of brain damage in PKU cases. However, we were also concerned with the possible cardiovascular risks caused by abnormal lipoprotein profiles. Place and Duration: Pak International Medical College, Hayatabad, Peshawar(PIMC) From Jan 2021 to December 2021 Study type: Case control study Methodology: Patients were asked for an overnight fast to get their plasma samples in the morning. Samples were frozen at − 20 °C to perform analysis by using a 600 MHz Bruker AVANCE IVDr spectrometer. For the statistical analysis, SPSS version 24.0 was used. A student t-test was applied to measure the statistical difference. The significant statistical difference was set as 0.05. Results: In case group total cholesterol was reported as 179.4 while the control group had 200.9 mg/dL with a p value < 0.02. On the other hand, the LDL cholesterol was reported as 104.1 mg/dL in control while 79.5 mg/dL in the case group with p<0.003. Meanwhile, no statistical difference was observed between both groups when comparing triglycerides. No statistical difference was observed between subclasses of lipoprotein. Furthermore in current research correlation was observed between blood PHE levels andPHE control diet. Conclusion: In conclusion, NMR spectroscopy provides unique patterns of lipoprotein profile which were previously seen in patients consuming statins as their treatment